Gambaran Pengetahuan Kesehatan Reproduksi Siswa SMK Wisnuwardhana Kota Malang - Kartikasari, Dhian; Ariwinanti, Desi; Hapsari, Anindya (Preventia: The Indonesian Journal of Public Health, 2019)
Adolescence is characterized by growth, development, and the emergence of opportunities to face reproductive health problems. Reproductive health problems that often arise are risky sexual behavior, pregnancy outside marriage, early marriage, abortion and sexually transmitted diseases such as HIV and AIDS. The results of the 2017 IDHS KRR show that knowledge of adolescent reproductive health in Indonesia is still low. This study aims to describe the reproductive health knowledge of adolescents in Wisnuwardhana Vocational School, Malang City. The number of samples was 44 students of Malang Wisnuwardhana Vocational School students who were taken by quota sampling. This type of research is descriptive research. The instrument used was a questionnaire to find out general respondents' data and questions about adolescent reproductive health. The results showed the number of respondents who had good knowledge was 9.1%, moderate knowledge was 81.1%, and knowledge was less than 9.1%. The average results of respondents' knowledge seen from gender factors have the results of male respondents having a higher average value of 8.8 than female respondents who have an average value of 8.1.